Characterizing the molecular features of ERG‐positive tumors in primary and castration resistant prostate cancer. Issue 9 (16th March 2016) - Roudier, Martine P.; Winters, Brian R.; Coleman, Ilsa; Lam, Hung‐Ming; Zhang, Xiaotun; Coleman, Roger; Chéry, Lisly; True, Lawrence D.; Higano, Celestia S.; Montgomery, Bruce; Lange, Paul H.; Snyder, Linda A.; et al.
Abstract : BACKGROUND: The TMPRSS2‐ERG gene fusion is detected in approximately half of primary prostate cancers (PCa) yet the prognostic significance remains unclear. We hypothesized that ERG promotes the expression of common genes in primary PCa and metastatic castration‐resistant PCa (CRPC), with the objective of identifying ERG‐associated pathways, which may promote the transition from primary PCa to CRPC. METHODS: We constructed tissue microarrays (TMA) from 127 radical prostatectomy specimens, 20 LuCaP patient‐derived xenografts (PDX), and 152 CRPC metastases obtained immediately at time of death. Nuclear ERG was assessed by immunohistochemistry (IHC). To characterize the molecular features of ERG‐expressing PCa, a subset of IHC confirmed ERG+ or ERG− specimens including 11 radical prostatectomies, 20 LuCaP PDXs, and 45 CRPC metastases underwent gene expression analysis. Genes were ranked based on expression in primary PCa and CRPC. Common genes of interest were targeted for IHC analysis and expression compared with biochemical recurrence (BCR) status. RESULTS: IHC revealed that 43% of primary PCa, 35% of the LuCaP PDXs, and 18% of the CRPC metastases were ERG+ (12 of 48 patients [25%] had at least one ERG+ metastasis). Based on gene expression data and previous literature, two proteins involved in calcium signaling (NCALD, CACNA1D), a protein involved in inflammation (HLA‐DMB), CD3 positive immune cells, and a novel ERG‐associated protein, DCLK1 were evaluated in primary PCa and CRPC metastases. In ERG+ primary PCa, a weak association was seen with NCALD and CACNA1D protein expression. HLA‐DMB association with ERG was decreased and CD3 cell number association with ERG was changed from positive to negative in CRPC metastases compared to primary PCa. DCLK1 was upregulated at the protein level in unpaired ERG+ primary PCa and CRPC metastases ( P = 0.0013 and P < 0.0001, respectively). In primary PCa, ERG status or expression of targeted proteins was not associated with BCR‐free survival. However, for primary PCa, ERG+DCLK1+ patients exhibited shorter time to BCR ( P = 0.06) compared with ERG+DCLK1− patients. CONCLUSIONS: This study examined ERG expression in primary PCa and CRPC. We have identified altered levels of inflammatory mediators associated with ERG expression. We determined expression of DCLK1 correlates with ERG expression and may play a role in primary PCa progression to metastatic CPRC. Prostate 76:810–822, 2016 . © 2016 Wiley Periodicals, Inc.